(untitled) (PerCursos, 2024)
This article recovers Gramsci’s (1891-1937) formulation about the Unitary School to problematize the limits of active pedagogies, of which Childhood Pedagogy is a tributary. The object of analysis is the main documents for the first stage of basic education, which guides the pedagogical work of the teachers in the Florianópolis Municipal Education Network: Pedagogical Educational Guidelines for Early Childhood Education (2010); Curricular Guidelines for Municipal Early Childhood Education (2012); Early Childhood Education Curriculum of the Florianópolis Municipal Education Network (2015). The analysis of these documents was carried with the contributions of Gramsci’s work, an essential communist revolutionary, who considered the need to overcome class society. The concepts of education and training for early childhood education and the limits of the child’s spontaneity were examined as a priority criterion in curricular organization, as opposed to directiveness as a tactical element in the process of cultural elevation of the masses. It is considered that the child’s spontaneity, however seductive it may seem, cannot prescind a directiveness anchored in the teacher, as the one who has the necessary conditions to socialize scientific knowledge - as a rule, denied to the working classes -, and confront spontaneous, folkloric knowledge, limited to common sense, in order to promoting critical formation in class society and providing the conditions to form leaders who will dispute hegemony for a classless society project.